2016
DOI: 10.4322/jms.098015
|View full text |Cite
|
Sign up to set email alerts
|

Histo-morphological study of a giant Meckel's diverticulum with gastric type of mucosa

Abstract: Introduction: Meckel's diverticulum or ileal diverticulum is one of the common congenital anomalies of the digestive system. It may not cause any problems in many, but may form serious life threatening complications in a few. Materials and Methods: We conducted a histo-morphological study of a giant Meckel's diverticulum found during cadaveric dissections of a South Indian adult male cadaver. The diverticulum was 7.5 cm long and had a circumference of 1.5 cm. Results: Gross anatomical and histological observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Akbulut and Yagmur have reported 8 cm long MD 16 whereas Nayak has reported 7.5 cm long. 17 In the current study it was 6 cm in length and ratio of hight to max diameter was <2. These findings suggest that the surgery is not required in this case.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Akbulut and Yagmur have reported 8 cm long MD 16 whereas Nayak has reported 7.5 cm long. 17 In the current study it was 6 cm in length and ratio of hight to max diameter was <2. These findings suggest that the surgery is not required in this case.…”
Section: Discussionmentioning
confidence: 51%
“…19 Many studies showed MD with ectopic gastric mucosa with symptom, without symptom or undiagnosed. 17,20 As age advances, the risk of developing complications decreases, however there are no predictive factors for the development of complications. 21,22 In the present study, tissues of diverticulum showed minor signs of inflammation, which denotes that mild complication had probably occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Meckel's diverticulum is the most common congenital anomaly of gastrointestinal tract with an average length of 3 cm [1 , 2] . This prevailing abnormality usually varies in size from 1 to 10 cm [3] .…”
Section: Introductionmentioning
confidence: 99%